World, European and National Policies in the Field of Cultural Tourism - Daniela Popa; Ioan Petroman; Cornelia Petroman; Virgil Lala; Dan Paicu; Loredana Heber; Diana Marin (Scientific Papers Animal Science and Biotechnologies, 2023)
At both world and national level, transnational policies in the field of tourism, in general, and of cultural tourism, in particular, come from the U.N.E.S.C.O. and from the W.T.O. represented by the U.N.O., while at European level these policies are exclusively the result of the European Union and of the European Council. National policies in the field of cultural tourism in Romania are developed by the Ministry of Tourism, and are included and detailed in the Master Plan for the Development of National Tourism. Though the number of associations, committees, councils, organisations, and other organisms dealing with world and European tourism is larger, at national level the National Authority of Tourism does not supply the necessary instruments to achieve sustainable development in the field of hospitality and of tourism, lacking marketing policies and coherent promotional strategies based on detailed understanding and on hierarchy of source markets.